2021
DOI: 10.1136/openhrt-2021-001763
|View full text |Cite
|
Sign up to set email alerts
|

FLOWER-MI and the root of the problem with non-culprit revascularisation

Abstract: How do we reduce cardiac death and myocardial infarction by percutaneous coronary intervention (PCI) in coronary heart disease? Although the interventional community continues to grapple with this question in stable angina, the benefits of PCI for non-culprit lesions found at ST-elevation myocardial infarction are established. Is it then wishful thinking that an index developed in stable coronary disease, for identifying lesions capable of causing ischaemia will show an incremental benefit over angiographicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…In our case, an evaluation with invasive physiology was not considered because it is contraindicated for blood vessels responsible for acute infarction (culprit lesions) due to microcirculation dysfunction and plaque instability. Moreover, several studies have shown that the analysis of physiology invasive therapy is clinically ineffective in this setting [19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…In our case, an evaluation with invasive physiology was not considered because it is contraindicated for blood vessels responsible for acute infarction (culprit lesions) due to microcirculation dysfunction and plaque instability. Moreover, several studies have shown that the analysis of physiology invasive therapy is clinically ineffective in this setting [19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%